2013
DOI: 10.1002/bit.24812
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of granulation process of activated sludge in sequencing batch reactors

Abstract: Aerobic granulation is a promising process for wastewater treatment, but this granulation process is very complicated and is affected by many factors. Thus, a mathematical model to quantitatively describe such a granulation process is highly desired. In this work, by taking into account all of key steps including biomass growth, increase in particle size and density, detachment, breakage and sedimentation, an one-dimensional mathematic model was developed to simulate the granulation process of activated sludge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…According to their model simulations, the optimal control strategy would be to keep the biomass discharge ratio between 0.01 and 0.05. This is in good agreement with the discharge ratio in R1 in our investigation, which hereby confirms experimentally that the control strategy proposed by Su et al [20] is indeed successful. Although R2 was operated with twice as high biomass discharge ratios during start-up (first 28 days), this approach was still effective in retaining biomass (Figure 2) while facilitating granulation.…”
Section: Biomass Retention and Granulationsupporting
confidence: 92%
See 2 more Smart Citations
“…According to their model simulations, the optimal control strategy would be to keep the biomass discharge ratio between 0.01 and 0.05. This is in good agreement with the discharge ratio in R1 in our investigation, which hereby confirms experimentally that the control strategy proposed by Su et al [20] is indeed successful. Although R2 was operated with twice as high biomass discharge ratios during start-up (first 28 days), this approach was still effective in retaining biomass (Figure 2) while facilitating granulation.…”
Section: Biomass Retention and Granulationsupporting
confidence: 92%
“…Therefore, to prevent severe biomass wash-out, or the formation of well-settling flocs instead of granules, a balanced strategy for decreasing the settling time is required during the start-up of granular sludge reactors. Su et al [20] suggested that a stepwise decrease of the settling time based on the biomass discharge ratio could be a successful strategy for achieving fast and effective granulation. According to their model simulations, the optimal control strategy would be to keep the biomass discharge ratio between 0.01 and 0.05.…”
Section: Biomass Retention and Granulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreasing size of granular sludge resulted in the decrease of settling velocity. Our results also agreed with Su et al (2013). In general, the granular sludge became fragile at pH 9.0 and a slight pH increase would lead to further damage on ANAMMOX system.…”
Section: Sludge Characteristicssupporting
confidence: 89%
“…Vazquez-Padín et al [27] showed that the biomass characteristics could be successfully described if a porosity profile across the granules depth was taken into account. Later, Su et al [28] modeled the variations in size and density of granules due to growth, detachment or breakage, to optimize the size and density of granules.…”
Section: Introductionmentioning
confidence: 99%